DETERMINAN SUSTAINABILITY DALAM KONSEP KEUANGAN EKONOMI KREATIF - Budi Prawoto; Tio Arriela Doloksaribu; Rizalnur Firdaus (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
One of the reasons for the decline of creative economy SMEs in the tourism sector during the pandemic is the limited financial resources owned by SMEs entrepreneurs. Capability in Entrepreneurial Financial Planning (Financial Sources, Structured Financing, Financial Performance) is an important requirement for starting and developing a business. This study discusses the problem of entrepreneurial finance for SMEs in Malang City. This study uses quantitative research methods with primary data obtained through an interview process. The research data obtained will be processed using the Structural Equation Model (SEM) method with SmartPLS data analysis. The results of the study show that the achievements of MSME sustainability are proven to be influenced by budgeting and financial reporting. The business development timeline has no effect on the sustainability of MSME businesses.